Multi-Aspiration Goal Programming Formulation - Karimi, Hossein; Attarpour, Mehdi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
A significant analytical approach contrived to solve many real-world problems is Goal Programming (GP). In many marketing or decision management problems, the phenomenon of multi-segment aspiration levels and multi-choice goal levels may exist for decision makers. This problem cannot be solved by current GP techniques such as multi-choice goal programming and multi-segment goal programming. This paper provides a new idea to integrate the multi-segment goal programming and multi-choice goal programming in order to solve multi-aspiration problems. Moreover, it develops the concepts of these models significantly for real application; in addition, a real problem is provided to demonstrate usefulness of the proposed model. The results of the problem are analyzed and finally, the conclusion is remarked.